Polyaniline Nano Films Synthesis in One Step via Chemical Oxidative Polymerization - Amal Shakir Abbood; Ibraheem Jaleel Ibraheem (Baghdad Science Journal, 2024)
Polyaniline films were successfully synthesized in this study using an oxidative polymerization method at temperatures ranging from 0 to 4 ° C. Polyaniline films were deposited using a single step of chemical oxidative polymerization rather than electrochemical polymerization. The polyaniline was examined using FTIR, XRD, SEM, AFM, and Four Point Probe. This result demonstrates that polyaniline synthesized using this method has a uniform morphology, small size (17 to 40) nm, high crystallinity, and high conductivity (9.42 s/cm).